Matchmakers : the new economics of multisided platforms - Evans, David S. 1954- (Harvard Business Review Press, 2016)
In Matchmakers, David Evans and Richard Schmalensee, two economists who were among the first to analyze multisided platforms and discover their principles, and who’ve consulted for some of the most successful platform businesses in the world, explain how matchmakers work best in practice, why they do what they do, and how entrepreneurs can improve their chances for success.